Tuberculosis Associated Septic Shock - Ida Bagus, Putra Narendra (International Journal of Scientific Research and Management (IJSRM), 2024)
Diagnosing and identifying the underlying disease of septic shock is so difficult, cases of tuberculosis-associated septic shock are extremely rare. A 55-year-old Woman with weakness, nausea, low intake, five episodes of diarrhea, three weeks of coughing, and a positive rapid molecular test result for tuberculosis. The patient had a history of AIDS and was receiving ARV treatment. There had also been a lump in the right neck for a month. A fine needle aspiration biopsy (FNAB) was performed, and the results showed a focus of atypical cells with a background of suppurative chronic inflammation. A physical examination revealed a fever (380C), blood pressure of 78/46 mmHg, and a pulse rate of 110 beats per minute. WBC: 2.60, HB: 7.5, HCT: 23.3, Plt: 353, SGOT/SGPT: 68/8, GDA: 142, BUN/SC: 108/2.6, Na: 141, K: 2.7, Cl: 107 were the results of the laboratory tests. The thorax x-ray revealed a pattern of miliary tuberculosis with a differential diagnosis of the metastatic.